Wicked problem definition and gradual institutional change: federalism and immigration in Canada and Australia. Issue 3 (14th August 2017) - Paquet, Mireille
Abstract: This article examines the impacts of problem definition, defined as a social mechanism, in bringing about gradual institutional change. Focusing on a similar process of gradual institutional change in Canada and Australia, it shows that problem definition is one pathway by which actors' interests and behaviors are redefined inside an institutional regime. By tracing the process of federalization of Canada and Australia's immigration regime since the 1990, it demonstrates that problem definition contributed to the rise of subnational governments as legitimate actors in the management of immigration. In these two countries, the specificities of the operation of this mechanism, including the actors mobilized for change, and the content of the policy problem being put forward generated different processes of federalization that nonetheless resulted in inclusive immigration federalism. In dialogue with historical institutionalism, this points to the potential of the mechanismic approach for theory building regarding the consequences of the dynamics of problem definition.